Principles of Education in the Perspective of the Qur'an: Theoretical Studies and its Development in the Modern Era - Novita, Vina; Arfizeah, Nurul Habibah; Alwizar (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
Islamic education is fundamentally oriented toward the formation of a complete human being (insān kāmil) who is faithful, knowledgeable, and has noble character. This study aims to examine the principles of Qur'anic education and their relevance to the modern education system. This study uses a qualitative approach with library research methods through thematic analysis of Qur'anic verses, tafsir books, and contemporary academic literature. The results show that the principles of Qur'anic education encompass the values of monotheism, knowledge ('ilm), morals, tazkiyyah (purification of the soul), balance (tawāzun), and insan kamil. These six principles emphasize the balance between intellectual, spiritual, and moral development of humans. The concept of tazkiyyah occupies a primary position because it is the foundation for the blessings of knowledge and morals, while tarbiyyah and ta'līm emphasize the process of comprehensive growth and teaching. The relevance of Qur'anic education to modern education lies in its shared orientation toward character formation, moral literacy, and the holistic development of human potential. The integration of revealed values and modern rationality results in an educational paradigm oriented toward a balance between knowledge, faith, and good deeds. Thus, Qur'anic educational principles contribute significantly to the renewal of the modern educational paradigm, particularly in strengthening the spiritual, moral, and humanistic dimensions amidst the global values crisis.